Outcomes of female and male patients suffering from coronary artery disease: A nation-wide registry of patients admitted as emergency. Issue 38 (24th September 2021) - Jäckel, Markus; Kaier, Klaus; Rilinger, Jonathan; Wolf, Dennis; Peikert, Alexander; Roth, Katrin; Oettinger, Vera; Dawid Leander, Staudacher; Zehender, Manfred; Bode, Christoph; Constantin, Von Zur Mühlen; Stachon, Peter
Abstract : Abstract: Presentation and mortality of coronary artery disease (CAD) substantially differs in both sexes. Most of the existing data analyzing sex differences is older than 10 years and mostly was retrieved in clinical trials, which are potentially structured with a bias against the inclusion of women, leading to a potential selection-bias. Meanwhile, with better diagnostic and therapeutic options, actual data analyzing sex differences in emergency CAD patients is rare. Data on all emergency case numbers with CAD diagnosis in Germany 2017 was retrieved from the German Institute for Medical Documentation and Information. DRG, OPS, and ICD codes were used to determine comorbidities, in-hospital course, and outcome. Competing risk regression analysis for in-hospital mortality was performed analyzing age, European System for Cardiac Operative Risk Evaluation (EuroSCORE), severity of CAD, clinical presentation type and sex. 264, 742 patients were included. Female patients were older and had more comorbidities. Three-vessel CAD was significantly less present in female patients (36.5% vs 47.5%; P < .001). After adjusting for age, EuroSCORE and severity of CAD, female sex was an independent predictor of lower in-hospital mortality (subdistribution hazard ratio [sHR] 0.94, 95% CI: 0.90–0.98, P = .002) in the whole cohort and in non-ST-segment elevation myocardial infarction (NSTEMI) patients (sHR 0.85, 95% CI: 0.79–0.92, P < .001), whereas in ST-segment elevation myocardial infarction (STEMI) patients, female sex was associated with a higher in-hospital mortality (sHR 1.07, 95% CI: 1.01–1.14, P = .029). In all patients admitted as emergency with CAD diagnosis and in all NSTEMI patients, female sex is protective, whereas in STEMI patients, females show a higher in-hospital mortality risk.